Carbothiolation of Styrenes by Visible‐Light‐Induced Thiyl Radicals: C3‐Functionalization of Benzofuran‐2(3H)‐ones. Issue 30 (8th August 2022) - Xi, Dailin; Lu, Cong; Jing, Dong; Zheng, Ke
Abstract: Thiyl radicals by far have taken part in manifold natural processes with regard to biochemistry. Utilizing their capability of reversibly adding onto carbon‐carbon double bond may be able to create valuable transformations. Herein, we report a novel thiyl radical precursor that can release sulfur‐centered radical by irradiation of visible light under mild conditions (without metals, photocatalysts, and other additives). A series of sulfur‐containing 3, 3‐disubstituted benzofuran‐2(3 H )‐ones were obtained with good functional group tolerance by thiol‐ene addition of styrenes with thiyl radicals. Mechanistic study confirmed the proposed process driven by EDA (Electron Donor‐Acceptor) complex. Abstract : A three‐component coupling reaction based on the novel precursor of thiyl radical was developed for constructing structurally valuable sulfur‐containing 3, 3‐disubstituted benzofuran‐2(3 H )‐one derivatives. The system is driven by EDA complex assembled between substrates, which means thiyl radical can be generated without external assistance, significantly highlighting the efficiency of this methodology.